2014
DOI: 10.1080/17470218.2014.897358
|View full text |Cite
|
Sign up to set email alerts
|

The Organization of Spatial Reference Frames Involved in the Snarc Effect

Abstract: The SNARC effect refers to faster reaction times for larger numbers with right-sided responses and for smaller numbers with left-sided responses, even when numerical magnitude is irrelevant. Although the SNARC is generally thought to reflect a mapping between numbers and space, the question of which spatial reference frame(s) are critical for the effect has not been systematically explored. We propose a dynamic hierarchical organization of the reference frames (from a global left-right frame to body-and object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
52
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(63 citation statements)
references
References 34 publications
10
52
1
Order By: Relevance
“…Such a relation was revealed as a culturally modulated preference to start finger counting from the left or right hand (Lindemann et al, 2011;see Wasner, Moeller, Fischer, & Nuerk, 2014 for situational influences on this pattern and Fischer, 2008 for relation between this preference and the SNARC effect), as an influence of the finger counting system on processing Arabic numbers (Domahs, Moeller, Huber, Willmes, & Nuerk, 2010), as an influence of number magnitude on left or right hand selection in a reach-to-grasp task (in school-aged children, Mills, Rousseau, & Gonzalez, 2014), as SNARC disappearance in a crossed hand condition (due to the conflict between number-button and number-hand assignment, Wood, Nuerk, & Willmes, 2006; see also Müller & Schwarz, 2007;Viarouge, Hubbard, & Dehaene, 2014 for task and instruction-dependent activation of manual reference frames for SNARC), etc. We see from this list that hand-and body-related reference frames for SNAs seem to be activated for a variety of tasks and number-space measures (cf.…”
Section: Implications For the Embodiment Theory Of Number-space Assocmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a relation was revealed as a culturally modulated preference to start finger counting from the left or right hand (Lindemann et al, 2011;see Wasner, Moeller, Fischer, & Nuerk, 2014 for situational influences on this pattern and Fischer, 2008 for relation between this preference and the SNARC effect), as an influence of the finger counting system on processing Arabic numbers (Domahs, Moeller, Huber, Willmes, & Nuerk, 2010), as an influence of number magnitude on left or right hand selection in a reach-to-grasp task (in school-aged children, Mills, Rousseau, & Gonzalez, 2014), as SNARC disappearance in a crossed hand condition (due to the conflict between number-button and number-hand assignment, Wood, Nuerk, & Willmes, 2006; see also Müller & Schwarz, 2007;Viarouge, Hubbard, & Dehaene, 2014 for task and instruction-dependent activation of manual reference frames for SNARC), etc. We see from this list that hand-and body-related reference frames for SNAs seem to be activated for a variety of tasks and number-space measures (cf.…”
Section: Implications For the Embodiment Theory Of Number-space Assocmentioning
confidence: 99%
“…We see from this list that hand-and body-related reference frames for SNAs seem to be activated for a variety of tasks and number-space measures (cf. Fischer & Brugger, 2011;Viarouge et al, 2014;Wood et al, 2006 for views which postulate multiple reference frames for number-space associations).…”
Section: Implications For the Embodiment Theory Of Number-space Assocmentioning
confidence: 99%
“…8, 1457-1460, http://dx.doi.org/10.1080/17470218.2014 The original discovery of left-to-right (e.g., Dehaene et al, 1993) and top-to-bottom (e.g., Ito & Hatta, 2004;Schwarz & Keus, 2004;Shaki & Fischer, 2012) associations between numbers and space raises the important issue of reference frames for these associations. Viarouge, Hubbard, and Dehaene (2014) investigated which spatial reference frames (world space, object space, or body space) are involved in the SNARC effect. Based on their findings, the authors propose a dynamic hierarchical organization of those spatial reference frames that can be modulated by experimental context.…”
mentioning
confidence: 99%
“…Previous work has shown that crossing the responding hands does not modulate the SNARC effect (Dehaene et al, 1993, Exp. 6), thus identifying an allocentric spatial reference frame (see also Viarouge, Hubbard, & Dehaene, 2014). In contrast, manual pointing is known to rely on egocentric spatial referencing, especially toward the end of the pointing trajectory (e.g., Fischer, Pratt, & Adam, 2007;Glover, 2004).…”
Section: Discussionmentioning
confidence: 99%